2006
DOI: 10.1111/j.1600-0609.2006.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F mutation in platelets from essential thrombocythemia patients: correlation with clinical features and analysis of STAT5 phosphorylation status

Abstract: The frequency of the JAK2V617F mutation in platelets was similar to that reported in granulocytes in the literature, suggesting this mutation does not occur as an isolated event in the megakaryocyte lineage. If confirmed in a larger study, the observed higher frequency of thrombosis in patients younger than 60 might be a useful predictive marker for thrombosis in this subset of patients. Even though this mutation has been predicted to constitutively activate the JAK2 kinase, spontaneous phosphorylation of STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
3
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 27 publications
5
48
3
2
Order By: Relevance
“…Soon after the description of the JAK2 V617F mutation, two retrospective analyses of 50 and 60 patients each with ET found that those with the mutation were more likely to have suffered from thrombosis 94,95 (Table 3). Besides, post hoc genetic analysis of the high-risk ET cohort in the Medical Research Council Primary Thrombocythemia-1 study demonstrated that the mutation was associated with higher Hb and white blood counts and that such patients had higher rates of venous thromboses.…”
Section: Prognostic Implications Of the Jak2 V617f Mutation In The Mpdsmentioning
confidence: 99%
“…Soon after the description of the JAK2 V617F mutation, two retrospective analyses of 50 and 60 patients each with ET found that those with the mutation were more likely to have suffered from thrombosis 94,95 (Table 3). Besides, post hoc genetic analysis of the high-risk ET cohort in the Medical Research Council Primary Thrombocythemia-1 study demonstrated that the mutation was associated with higher Hb and white blood counts and that such patients had higher rates of venous thromboses.…”
Section: Prognostic Implications Of the Jak2 V617f Mutation In The Mpdsmentioning
confidence: 99%
“…The RARA gene portion of the fusion gene products ought to be from exon 3, and the fusion gene products must form homodimers as well as repress retinoic acid-responsive transcriptional activity. 3,4 We hereby report the cloning of a seventh fusion gene from an APL variant and the functional characterization of its product.…”
Section: 2mentioning
confidence: 99%
“…[8][9][10][11][12][13][40][41][42][43][44][45] Because JAK2V617F is myeloid neoplasm-specific and not found in other causes of polycythemia, [46][47][48] it has lent itself to being a sensitive diagnostic marker for PV. 44 However, in the context of myeloid neoplasms, JAK2V617F is not specific for PV and is found in approximately 50% of patients with ET, [49][50][51][52][53][54]56 or RARS-T, [57][58][59][60][61] and at a lesser frequency in other myeloid neoplasms, [62][63][64][65][66][67][68][69][70] but not in lymphoid tumors. 46,[71][72][73] Therefore, mutation screening for JAK2V617F cannot be used to distinguish one MPN from another, but it does complement histology in the diagnosis of both ET and PMF by excluding the possibility of reactive thrombocytosis or myelofibrosis (Table 2).…”
Section: Introductionmentioning
confidence: 99%